GREEN VISION DALAM TRADISI KEARIFAN SYARIAH ISLAM - Mudhofir Abdullah (IBDA` : Jurnal Kajian Islam dan Budaya, 2012)
This article discusses the environmental wisdom in Islam whichcomes from al-Qur’an and Hadis. The nature concept in Syariah is generalso the new meaning and the detail need to be given in order to bemore operational. The discussion on tafsir and fikih is held by using jurisprudenceor us}u>l al-fiqh and historical approach. The teaching on environmentalwisdom in Syariah and the concept of protecting the wisdomare the focuses of this research. This article shows that mas}lah}ah principlehas proved to strengthen the argument of Syariah protection towardenvironment. This principle also proposes new tradition, h}ima> (inviolatezone/protected area) as the conservation activity. Green vision inSyariah tradition based on ikra>m or a respect to the nature’s rights whichshould be kept and obeyed by every khali>fah.